2021
DOI: 10.1186/s12875-021-01463-3
|View full text |Cite
|
Sign up to set email alerts
|

Information meetings on end-of-life care for older people by the general practitioner to stimulate advance care planning: a pre-post evaluation study

Abstract: Background To increase knowledge about options people have concerning end-of-life-care issues, General Practitioners (GPs) can organise meetings to inform their older patients. We evaluated these meetings, using the following research questions: How did the attendees experience the information meeting? Was there a rise in Advance Care Planning (ACP) behaviour after the information meeting? Was there a change in trust people have that physicians will provide good care at the end of life and that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In our study, most older adults had thought about ACP topics during COVID-19, but had not discussed them with a physician. Two other studies among Dutch older adults aged 75 years and above (before COVID-19), using different Dutch data, found similar prevalence regarding ACP [ 16 , 17 ]. These two studies also found that most older adults think about ACP topics, however that discussing ACP with a physician is still not that common [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…In our study, most older adults had thought about ACP topics during COVID-19, but had not discussed them with a physician. Two other studies among Dutch older adults aged 75 years and above (before COVID-19), using different Dutch data, found similar prevalence regarding ACP [ 16 , 17 ]. These two studies also found that most older adults think about ACP topics, however that discussing ACP with a physician is still not that common [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 74%
“…Two other studies among Dutch older adults aged 75 years and above (before COVID-19), using different Dutch data, found similar prevalence regarding ACP [ 16 , 17 ]. These two studies also found that most older adults think about ACP topics, however that discussing ACP with a physician is still not that common [ 16 , 17 ]. However, also discussing your preferences and wishes with a physician is found to be important for receiving end-of-life care in accordance with preferences and preventing unnecessary and undesirable hospital admissions [ 18 ].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…For instance, in the Netherlands, research showed that inviting older adults to information sessions about EOL healthcare led by general practitioners can positively impact individuals' engagement in ACP. 59 The authors further explained that although this approach mainly resonates with older individuals already curious about the topic, it appears to be a straightforward way to encourage ACP. 59 It is also crucial to enlighten healthcare providers about the significance of assessing the health competency level of patients concerning EOL healthcare.…”
Section: Practical Implications and Future Researchmentioning
confidence: 99%
“…59 The authors further explained that although this approach mainly resonates with older individuals already curious about the topic, it appears to be a straightforward way to encourage ACP. 59 It is also crucial to enlighten healthcare providers about the significance of assessing the health competency level of patients concerning EOL healthcare. This would enable them to tailor their communication, fostering better understanding between patients and healthcare providers.…”
Section: Practical Implications and Future Researchmentioning
confidence: 99%